Desired Characteristics of Professional Educational Administrators Under Lopburi Primary Educational Service Office, Area 2 - Yuangthong, Ratthaphum; Phayom, Choochart; Chulasukhont , Phuwadon (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
The purposes of this study were: 1. to investigate the desirable characteristics of professional school administrators in schools under the Lopburi Primary Educational Service Area Office 2, and 2. to compare the desirable characteristics of professional school administrators in schools under the same office, classified by gender, marital status, position, educational level, and work experience. The sample for this study consisted of 296 school administrators and teachers from schools under the Lopburi Primary Educational Service Area Office 2 for the 2023 academic year. Participants were selected through proportional stratified random sampling. The data collection instrument was a 15-item questionnaire. The statistical methods used for data analysis included mean, standard deviation, t-test, and one-way analysis of variance (ANOVA). The results of the study revealed that: 1. The desirable characteristics of professional school administrators in schools under the Lopburi Primary Educational Service Area Office 2 were rated as high both overall and in each specific area, and 2. When comparing the desirable characteristics of professional school administrators by gender, marital status, position, educational level, and work experience, no statistically significant differences were found.